Heparin-Binding Haemagglutinin, a New Tool for the Detection of Latent Mycobacterium tuberculosis Infection in Hemodialysis Patients - Dessein, Rodrigue; Corbière, Véronique; Nortier, Joëlle; Dratwa, Max; Gastaldello, Karine; Pozdzik, Agnieszka; Lecher, Sophie; Grandbastien, Bruno; Locht, Camille; Mascart, Françoise (PloS one, 2013)
Patients with end-stage renal disease (ESRD) and latently infected with Mycobacterium tuberculosis (LTBI) are at higher risk to develop tuberculosis (TB) than healthy subjects. Interferon-gamma release assays (IGRAs) were reported to be more sensitive than tuberculin skin tests for the detection of infected individuals in dialysis patients. On 143 dialysis patients prospectively enrolled, we compared the results from the QuantiFERON®-TB Gold assay (QFT), to those of an IGRA in response to in vitro stimulation of circulating mononuclear cells with the mycobacterial latency antigen Heparin-Binding Haemagglutinin purified from Mycobacterium bovis BCG (native HBHA, nHBHA). Seven patients had a past history of active TB and 1 had an undetermined result with both IGRAs. Among the other 135 patients, 94 had concordant results with the QFT and nHBHA-IGRA, 40.0% being negative and therefore not latently infected, and 29.6% being positive and thus LTBI. Discrepant results between these tests were found for 36 patients positive only with the nHBHA-IGRA and 5 only with the QFT. The nHBHA-IGRA is more sensitive than the QFT for the detection of LTBI dialysis patients, and follow-up of the patients will allow us to define the clinical significance of discrepant results between the nHBHA-IGRA and the QFT.